2012
DOI: 10.5812/anesthpain.3404
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Control for Total Knee Arthroplasty: Continuous Femoral Nerve Block Versus Intravenous Patient Controlled Analgesia

Abstract: In total knee arthroplasty, postoperative pain control is imperative in facilitating physical therapy and rehabilitation. Our study promotes use of continuous femoral nerve blocks for pain relief post total knee arthroplasty. ambulation, which hastens recovery and reduces hospital length of stay (5). The risk of postoperative complications, such as venous thromboembolism and nosocomial infections (6), has also been shown to decrease with early mobilization.Pain control modalities for post-TKA include intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Effective postoperative pain therapy and early mobilization has a significant influence on patient’s satisfaction and the spectrum of complications after implantation of a knee arthroplasty (TKA). A proven and effective principle is to perform regional anesthesia using an isolated and combined femoral and/or sciatic nerve block (FNB or SNB) with or without a permanent catheter [ 7 , 8 , 10 , 11 , 15 , 18 ]. A combined pain medication therapy with opioid analgesics and non-steroidal anti-inflammatory drugs (NSAIDs, cyclooxygenase cox inhibitors) can be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Effective postoperative pain therapy and early mobilization has a significant influence on patient’s satisfaction and the spectrum of complications after implantation of a knee arthroplasty (TKA). A proven and effective principle is to perform regional anesthesia using an isolated and combined femoral and/or sciatic nerve block (FNB or SNB) with or without a permanent catheter [ 7 , 8 , 10 , 11 , 15 , 18 ]. A combined pain medication therapy with opioid analgesics and non-steroidal anti-inflammatory drugs (NSAIDs, cyclooxygenase cox inhibitors) can be performed.…”
Section: Introductionmentioning
confidence: 99%
“…They have concomitant psychological disorders and abnormal pain sensitivity (3). Although opioids have been used for a long time as postoperative analgesia, the current trend is shifting to non-opioid analgesia (4)(5)(6), multimodal analgesia (7), and regional nerve blocks (8). In 1957, haloperidol, the first butyrophenone, was synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative pain management is an important part of postoperative care and plays an important role in postsurgical ambulation and general status of patients ( 1 - 4 ). Also, perioperative pain can adversely affect patient’s hemodynamic status, and increase the risk of several cardiovascular complications like myocardial infarction and cerebrovascular accidents such as stroke, and etc.…”
Section: Introductionmentioning
confidence: 99%
“…To decrease these complications, other nonopioid medications can be used to relieve pain before the operation ( 9 - 13 ) or after it ( 14 , 15 ). Peripheral tissue damage and subsequent inflammatory response cause a local change in sensitivity of peripheral receptors and increase the excitability of neurons present in the spinal cord ( 2 , 4 ). Studies have demonstrated that N-methyl-D-aspartate receptors (NMDA) play a part in increasing the sensitivity of spinal receptors ( 15 ).…”
Section: Introductionmentioning
confidence: 99%